2000
DOI: 10.1039/a908542d
|View full text |Cite
|
Sign up to set email alerts
|

Nano-electrospray and microbore liquid chromatography-ion trap mass spectrometry studies of copper complexation with MHC restricted peptides

Abstract: The formation of copper/peptide complex ions by nano-electrospray and microbore HPLC-electrospray mass spectrometry has been investigated for major histocompatibility complex (MHC) class I and class II restricted peptides. Post-column addition of copper(II) acetate following microbore HPLC-MS separation was carried out using a mixing T-piece or via the sheath flow inlet of the electrospray source. Optimal analytical conditions for copper complex ion formation were determined by variation of copper concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…In addition to the above interpretation of the behavior of these Cu II complexes in the ESI source, we explored the possibility of direct Leu/Ile differentiation from the in‐source dissociations of such complexes by liquid chromatography coupled with an ESI ion trap mass spectrometer. In this experiment the complexation metal reagent is introduced after the analytical column by use of a syringe pump 31,43. Similar trends were obtained under LC/ESI‐MS conditions as in the direct infusion mode, even though the composition of the CH 3 CN/H 2 O solvent mixture is modified during the separation gradient.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…In addition to the above interpretation of the behavior of these Cu II complexes in the ESI source, we explored the possibility of direct Leu/Ile differentiation from the in‐source dissociations of such complexes by liquid chromatography coupled with an ESI ion trap mass spectrometer. In this experiment the complexation metal reagent is introduced after the analytical column by use of a syringe pump 31,43. Similar trends were obtained under LC/ESI‐MS conditions as in the direct infusion mode, even though the composition of the CH 3 CN/H 2 O solvent mixture is modified during the separation gradient.…”
Section: Resultsmentioning
confidence: 52%
“…The metallation of these peptides was explored in LC/MS experiments by post‐column addition of a solution of a divalent metallic cation salt introduced using a syringe pump via a tee‐piece located between the analytical column and the ESI source. The CuCl 2 salt solution (32 mM, flow rate 1200 μL/min) was adjusted to pH 11 by adding NH 4 OH for an improvement of the metallation yield, as described by Creaser and co‐workers 31. The YGGFL and YGGFI enkephalins (24 pmol/μL of each peptide, 10 μL injected) were separated on a C 18 column (Zorbax stable Bond, 2.1 × 150 mm) by an elution gradient from 80–20% to 50–50% (H 2 O/CH 3 CN) in 8 min.…”
Section: Methodsmentioning
confidence: 99%
“…As a consequence, under typical operating conditions, only a single stage of tandem mass spectrometry may be available using these techniques, limiting their scope for the analysis of complex oligosaccharides. In contrast, it has been demonstrated that the quadrupole ion trap is a useful tool for the analysis of biomolecules such as peptides,31–33 oligonucleotides34,, 35 and oligosaccharides,13,, 14 through the use of successive stages of trapping and CAD to reveal structural details that cannot be resolved by MS/MS alone.…”
mentioning
confidence: 99%
“…There was also negligible leaching of Cu(II) ions, indicated by the absence of Cu(II)-peptide adducts, which are detectable by ESI [29]. In addition, Cu(II) ion leakage was minimised by underloading the metal ion on the Poros media.…”
Section: Analysis Of a Bsa Tryptic Digestmentioning
confidence: 97%
“…This peptide does not contain a histidine residue, but the sequence includes tryptophan. It has previously been shown that the tryptophan indole side chain shows some affinity for Cu(II) ions [29], but to a lesser extent than histidine. In comparison to the mass spectrum obtained without IMAC separation (Fig.…”
Section: Analysis Of a Bsa Tryptic Digestmentioning
confidence: 99%